2018
DOI: 10.1021/acs.jpcc.8b06797
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the “Subtle Interplay” between Intermolecular and Molecule–Substrate Interactions in Molecular Assembly on Surfaces

Abstract: The effect of the concurrent action of intermolecular and molecule−substrate interactions on the two-dimensional (2D) self-assembly of organic molecules on solid surfaces is investigated in a combined experimental and theoretical effort. Scanning tunneling microscopy measurements of terephthalic acid on the Cu(111) surface, a model system where the interplay between the two interactions is particularly evident, are used to develop a general, simple, and computationally inexpensive model that quantitatively acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 63 publications
1
14
1
Order By: Relevance
“…Their apparent depth is about 50 pm for a bias voltage of 100 mV. These dark contrasts look like those presented by White et al 17 for TPA on Cu(111) but without the structural difference reported by these authors. Indeed, during our experiments, the intermolecular distances around the defects remain identical to those measured in the pristine lattice.…”
Section: Evolution Of the Self-assemblysupporting
confidence: 85%
See 2 more Smart Citations
“…Their apparent depth is about 50 pm for a bias voltage of 100 mV. These dark contrasts look like those presented by White et al 17 for TPA on Cu(111) but without the structural difference reported by these authors. Indeed, during our experiments, the intermolecular distances around the defects remain identical to those measured in the pristine lattice.…”
Section: Evolution Of the Self-assemblysupporting
confidence: 85%
“…Physisorption of single TPA also results in the absence of spectroscopic features that could be due to the molecule electronic levels (contrary to the selfassemblies where the metallic surface state is shifted above the Fermi level and becomes an interface state). The electronic surface state around the molecules is not disturbed, contrary to what is observed on Cu(111) where dark depressions appear on the molecule extremities simply after their adsorption on the susbtrate 17 .…”
Section: Experiments At the Single Molecule Levelcontrasting
confidence: 66%
See 1 more Smart Citation
“…A possible reason for this may be the effect of the substrate, i.e. the relationship between the substrate periodicity and the intra-chain periodicity, 71 and the possibility of inter-chain interactions (either weak or strong, depending on the presence of OH groups) modulating the substrate interactions.…”
Section: Stm Imagingmentioning
confidence: 99%
“…In many cases, the molecule-substrate interaction has been recognized to be governed by the electronic structure of the substrate, which, in turn, impacts the structural properties of self-assembled nanomaterials on various substrates; e.g., bulk metals [9][10][11][12][13][14][15], twodimensional materials [16,17], and polar oxide surfaces [18][19][20]. Tuning the subtle balance between molecule-molecule and molecule-surface interactions [21] has opened up new pathways for creating an impressive variety of molecular structures on surfaces [22][23][24][25][26]. For example, structures ranging from perfectly ordered two-dimensional layers [27], unidirectional rows [28,29], porous networks [30,31] to complex structures have been presented as a function of the specific molecular design [27,32,33].…”
Section: Introductionmentioning
confidence: 99%